2010
DOI: 10.1016/j.jtbi.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological modeling of tumor diameter growth based on a mixed effects model

Abstract: Over the last few years, taking advantage of the linear kinetics of the tumor growth during the steady-state phase, tumor diameter-based rather than tumor volume-based models have been developed for the phenomenological modeling of tumor growth. In this study, we propose a new tumor diameter growth model characterizing early, late and steady-state treatment effects. Model parameters consist of growth rhythms, growth delays and time constants and are meaningful for biologists. Biological experiments provide in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…This transformation is similar to the one previously proposed [32] to obtain a quasi-linear steady-state behaviour of the CI profile. To benefit from all the information contained in the TCI profiles, we propose to analyze them by a parametric model and to analyze the parameters as global characteristics of the complete in vitro response.…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…This transformation is similar to the one previously proposed [32] to obtain a quasi-linear steady-state behaviour of the CI profile. To benefit from all the information contained in the TCI profiles, we propose to analyze them by a parametric model and to analyze the parameters as global characteristics of the complete in vitro response.…”
Section: Methodssupporting
confidence: 58%
“…The CI variable was firstly transformed into a new modeling variable called transformed cell index (TCI) to obtain quasi-linear steady-state behaviour of the CI profile. Such a variable transformation was already applied to in vivo data for tumor response modeling [32]. We showed that an exponential-linear equation can describe all the measured TCI kinetics profiles.…”
Section: Resultsmentioning
confidence: 99%
“…These values are obtained by using some numerical approximations and data from the literature [1,[8][9][10][11][17][18][19][20][21][22][23][24][25][26][27][28][29]. Furthermore, the volume of a cell is approximated by a mean cell sphere with the diameter,…”
Section: The Thermodynamic Approachmentioning
confidence: 99%
“…For instance, the tumor control probability (TCP) (Zaider and Minerbo, 2000;Dawson and Hillen, 2006;Gay and Niemierko, 2007) and the normal tissue complication probability (NTCP) (Lyman, 1985;Kallman et al, 1992) are used to characterize and evaluate the radiotherapy treatment planning. Their mathematical expressions can be derived from different stochastic models of the tumor response such as the linear quadratic model (Fowler, 1989;Zaider and Minerbo, 2000), cell populationdynamic models (Sachs et al, 2001), mixed-effects behavioral models (Bastogne, 2010) and cell cycle models (Kirkby et al, 2002). The main drawback of those mathematical representations is their inability to handle biological heterogeneity.…”
Section: Introductionmentioning
confidence: 99%